Grasping knowledge, attitude, and perception towards monkeypox among healthcare workers and medical students: an Egyptian cross-sectional study - Amer, Fatma A.; Nofal, Hanaa A.; Gebriel, Manar G.; Bedawy, Aya M.; Allam, Ayman A.; Khalil, Hend E. S.; Elahmady, Mohammed; Nofal, Hagar; Saeed, Maysaa A.; Shaltout, Shaker Wagih; Behiry, Ahmed; Attia, Osama; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Monkeypox (Mpox) is a re-emerging infectious disease representing a new global challenge. It poses a substantial threat to countries, particularly those with a low number of cases. Due to its popularity as a tourist destination and its proximity to many African refugees, Egypt is potentially at risk of Mpox importation. Therefore, effective disease management necessitates healthcare workers (HCWs) to possess adept knowledge, along with a positive attitude and behavior. The study aimed to assess the knowledge, attitude, and perception of Egyptian HCWs and medical students towards human Mpox. Methods: The present cross-sectional study data was collected from participants between October and December 2022 via a questionnaire. The questionnaire comprised 31 questions in the knowledge section, 11 questions in the attitude section, and 14 in the perception section. Results: The present study involved a total of 1,034 HCWs and medical students. It was found that 55.3% of the participants demonstrated adequate knowledge about mpox, whereas 44.5% and 39.8% of the respondents exhibited favorable attitudes and perceptions towards the disease, respectively. Binary logistic regression analysis revealed that adequate knowledge was significantly observed in ages older than 40 years (p < 0.001), married participants (p < 0.001), and doctors (p < 0.001). The positive attitude was significantly observed among the male sex (p = 0.045), urban residents (p = 0.002), and nurses (p = 0.002). Conversely, married participants (p = 0.013), doctors (p < 0.001), and individuals employed in pharmacy and laboratory departments (p < 0.001) experienced an increase in positive perception. Conclusion: Knowledge, attitude, and perception towards Mpox among Egyptian HCWs and medical students exhibit suboptimal levels. Addressing these gaps is crucial to controlling and effectively preventing disease transmission.